Immunogenicity of a two-dose investigational hepatitis B vaccine, HBsAg-1018, using a toll-like receptor 9 agonist adjuvant compared with a licensed hepatitis B vaccine in adults. Issue 5 (29th January 2018) - ,; Adams, Michael; Bolshoun, David; Bruce, Tami; Chuang, Rita; DeSantis, Donna; Fiel, Thomas; Fitzgibbons, William; Francyk, David; Geisberg, Harry; Giep, Son; Godbole, Narendra; et al.
Highlights: Phase 3 trial of an investigational 2 dose hepatitis B vaccine in diabetes mellitus. 2 doses of HBsAg-1018 induced significantly higher seroprotection rates than HBsAg-Eng. HBsAg-1018 demonstrated better consistency of SPRs in subpopulations than HBsAg-Eng. Abstract: Background: Hepatitis B virus infection remains an important public health problem in the United States. Currently approved alum-adjuvanted vaccines require three doses and have reduced immunogenicity in adults, particularly in those who have diabetes mellitus, or are older, male, obese, or who smoke. Methods: Phase 3 observer–blinded, randomized (2:1 HBsAg-1018 [HEPLISAV-B™]:HBsAg-Eng [Engerix-B®]), active–controlled trial in adults 18–70 years of age. HBsAg-1018 was administered intramuscularly at weeks 0 and 4 and placebo at week 24 and HBsAg-Eng at weeks 0, 4, and 24. The primary immunogenicity endpoint assessed the noninferiority of the seroprotection rate at week 28 in participants with type 2 diabetes mellitus. Secondary endpoints included seroprotection rates in the total trial population and by age, sex, body mass index, and smoking status. Results: Among 8374 participants randomized, 961 participants in the per-protocol population had type 2 diabetes mellitus. In diabetes participants, the seroprotection rate in the HBsAg-1018 group at week 28 was 90.0%, compared with 65.1% in the HBsAg-Eng group, with a difference of 24.9% (95% CI: 19.3%, 30.7%), which met the prospectively-defined criteria for noninferiority and statistical significance. In the total study per-protocol population (N = 6826) and each pre-specified subpopulation, the seroprotection rate in the HBsAg-1018 group was statistically significantly higher than in the HBsAg-Eng group. Conclusion: Two doses of HBsAg-1018, administered over 4 weeks, induced significantly higher seroprotection rates than three doses of HBsAg-Eng, given over 24 weeks, in adults with factors known to reduce the immune response to hepatitis B vaccines as well as in those without those factors. With fewer doses in a shorter time, and greater immunogenicity, HBsAg-1018 has the potential to significantly improve protection against hepatitis B in adults at risk for hepatitis B infection. Trial Registrationclinicaltrials.gov Identifier: NCT02117934.